Involvement of CD95 and ligand in CD4+ T-cell and CD8+ T-cell depletion and hepatic cytolysis in patients with chronic viral hepatitis B - Franklin S. Azebaze Agueguia; Paul Talla; Marie C. Okomo Assoumou; Graeme B. Jacobs; Cedric H. Mbakam; Elise Guiedem; Martha Tongo Mesembe; Emilia Lyonga; George Mondinde Ikomey (AOSIS, 2021)
Background: Chronic viral hepatitis B (HBV) is characterised by progressive hepatocyte destruction and T-cell depletion. The mechanisms of the CD95-CD95 ligand (CD95L) signalling pathway during this chronic disease and the cirrhotic process remains unclear. Objective: We evaluated the involvement of the CD95-CD95L receptor-ligand system in T-cell depletion and hepatic cytolysis in patients with chronic HBV. Methods: This was a cross-sectional study conducted from September to December 2018 at the Yaoundé General Hospital, Cameroon. Four mL of whole blood was collected and analysed. The CD95 and CD95L levels, as well as the CD4+ T-cell and CD8+ T-cell counts, were performed by enzyme-linked immunosorbent assay and flow cytometry. Results: Of the 130 HBV-positive patients, 36 (27.7%) were cirrhotic and 94 (72.3%) were non-cirrhotic. The cirrhotic patients had significantly elevated CD95 (p 0.001) and CD95L (p = 0.001) plasma levels, compared with non-cirrhotic patients. The CD4/CD8 ratios were lower in cirrhotic patients, compared to non-cirrhotic patients (p 0.001). There were statistically significant correlations between CD95 level and CD4+ T-cell counts, between CD95 level and CD8+ T-cell counts, between CD95 level and the CD4/CD8 ratio, between CD95 level and fibrosis score, and between CD95L level and fibrosis score. Conclusion: CD95 and CD95L could be involved in T-cell depletion and hepatic cytolysis during the pathogenesis of chronic HBV and could potentially be used as biomarkers for immunological and hepatic monitoring in patients with chronic HBV.